促進敘述性、假設性和理論性科學概念建構之數位論證研究 - 佘曉清; SHE HSIAO-CHING (My University, 2013)
研究者曾針對小組論證進行概念改變研究（Yeh & She, 2010; Chen & She, in press） 顯示有效的提升學生論證能力與概念的改變。截至目前為止未曾有研究針對比較個人 與小組論證進行深入探討比較研究。因此研究者非常有興趣研究當提供給兩組同樣的 論證鷹架時，個人論證與小組論證對於學生科學概念建構孰優孰劣？許多研究直接或 間接的指出科學論證的品質與科學知識的豐富有緊密的關係，因此，研究者試圖要探 討提供給學生相關科學知識的資料的提示與否，對於學生的論證品質與科學概念建構 的影響為何？除此之外，論證的施行與成效是否因敘述性(Descriptive)、假設性 (Hypothetical)、和理論性(Theoretical)概念種類不同而有差異，其概念建構的成效是否 有差異。 第一年：完成開發可以協助學生經由論證建構敘述性(Descriptive)、假設性 (Hypothetical)、和理論性(Theoretical)概念之個人與小組兩套科學論證數位學習平台。 該系統平台的發展包括提供論證鷹架協助學生論證，提供學生論證學習之相關科學知 識的數位內容，建立記錄所有電腦螢幕上論證學習歷程的程式，並進行測試與修正這 些這論證數位學習平台之論證功能。並完成一個主題的科學論證模組設計並置入數位 論證平台與在兩個班分成個人和小組進行科學的數位論證學習。同時開始著手發展部 分的敘述性(Descriptive)、假設性(Hypothetical) 、和理論性(Theoretical)概念等三類科 學概念之科學論證數位學習課程內容。 第二年：繼續發展敘述性(Descriptive)、假設性(Hypothetical) 、和理論性 (Theoretical)等三類科學概念之科學論證數位學習課程內容。將三類科學概念之科學 論證數位學習內容置入數位論證學習系統。同時發展生物和理化相關概念相依論證測 驗、生物與理化概念二階測驗等四份測驗工具。 第三年：並將敘述性(Descriptive)、假設性(Hypothetical)、和理論性(Theoretical) 理化、生物概念數位論證學習模組，正式用於中學理化、生物學習，並進而探討個人 和小組學生在三種不同類別科學概念之論證與概念建構情形。深入分析學生在生物與 理化之敘述性、假設性和理論性概念的數位論證品質與不同類型概念建構影響。 相信此研究的結果，可以提供我們深入的瞭解對於運用相同的論證鷹架時，個 人論證與小組論證對科學概念建構與論證的品質之影響。更進一步瞭解有無提供學生 相關科學知識的資料提示，對於學生的論證品質與科學概念建構的影響。除此之外， 論證的施行與成效是否因敘述性(Descriptive)、假設性(Hypothetical)、和理論性 (Theoretical)概念種類而有不同。

Several previous studies have indicated that on-line scientific group argumentaion can efficently promoting students argumentation and conceputal change ( Yeh & She, 2010; Chen & She, in press). It has not been examined whehter group argumentaion would be superior than to the individual argumentation. Therefore, the author is interesting to investigate whether group argumentaion would benefit students more than to the individual argumentation, regardless of argumentation ability or scientific concepts construction. On the other hand, many studies have directly or indirectly indicated the relationships existed between argumentation and sceintific knowledge. Therefore, the author would like to explore the impact on argumentation with or without providing supplemenary of scientific knowledge resources. Besides, the author is also curious how is the impact of argumentation on the nature and extent of descriptive, hypothetical, and theoretical concepts construction. The guideline for the following three years would be: First year: develop individual and group argumentation two on-line learning systems to facilitate students construction of descriptive, hypothetical and theoretical scientific concepts. The system provides students with scaffoldings of argumentation and necessary scientific knowledge resources for construction of descriptive, hypothetical and theoretical scientific concepts, and the fuction of recording students argumentation process and dialougs. Morevoer, develop a training module for training students on-line arugmentation. In addition, we also start to develop a series of descriptive, hypothetical and theoretical biology and physical science learning modules. Second year: continue to develop a series of descriptive, hypothetical and theoretical biology and physical science on-line argumentation learning modules；and setup all of these learning modules at the on-line argumentation system. In addition, develop biology and phyical science concepts two-tier tests and biology and physical science concept-dependent argumentation tests in order to measure the effectiveness of argumentation. Third year: Formally implement a series of descriptive, hypothetical and theoretical biology and physical science on-line argumentationlearning modules. Analyze the data collected from descriptive, hypothetical and theoretical biology and physical science on-line argumentationlearning modules by four different conditions, individual argumentation with scientific knoweldge resources, individual argumentation without scientific knoweldge resources, group argumentation with sceintific knoweldge resources, and group argumentation withou sceintific knoweldge resources. It is hoping to exmine the nature and extent of argumentation and descriptive, hypothetical and theoretical biology and physical science concepts construction after the use of indvidual vs. group argumentation. It is believed that the result of this study would provide us better understanding regarding to whether with or without scientific knoweldge resources influence on argumentation and scientific concept construction. It also would provide us more in-depth understanding the impact on students argumentation and concept construction between individual and group arugmentation. Morevoer, to get clear understanding the effectiveness of constructing descriptive, hypothetical and theoretical concepts construction through four different on-line argumentation conditions.
Enhancing Descriptive, Hypothetical and Theoretical Scientific Concepts Construction through On-line Argumentation